Elements of the built environment that can promote physical activity in elderly: an umbrella review. (30th September 2020) - Manzi, F; Del Riccio, M; Naldi, E; Setola, N; Dellisanti, C; Lorini, C; Bonaccorsi, G
Abstract: Background: All healthy adults aged 65 years and above, unless specific medical conditions, benefit from physical activity. The built environment can support and encourage physical activity. The aim of this study is to establish which specific elements of the built environment can contribute to improve the physical activity of self-sufficient, non-institutionalized and living in the city adults > 65 years. Methods: An extensive literature search was conducted in several database. Umbrella review methodology was used to include the systematic reviews that presented a sufficient methodological quality. Data from reviews were undergone to critical appraisal, data extraction and synthesis. Results: Eleven reviews were included. The elements positively associated with physical activity in the elderly resulted: walkability; residential density/urbanisation; street connectivity; access/availability of services and destinations (land-use mix destination diversity and access, public transit, recreational facilities, parks and open spaces); pedestrian/cycling infrastructures and streetscapes (footpaths presence and quality, infrastructures for walking or cycling, easy access to building entrance, benches and sitting facilities, street lights); greenery and aesthetically pleasing scenery; safety and traffic (crime, personal and general safety, traffic and pedestrian safety, human or motorised traffic volume). The elements that resulted as negatively associated with physical activity were: the presence of slopes or hilliness; presence of barriers to walking/cycling; littering/vandalism/decay/vacant buildings; pollution (air, noise, sewer). Conclusions: Evidences show that specific elements of the built environment can contribute to promoting elderly people's physical activity. The city restructuring plans should take into consideration these evidences in order to implement the design of interventions aimed at promoting physical activity of elderly people. Key messages: Evidences show that specific elements of the built environment can contribute to promoting elderly people's physical activity. The city restructuring plans should take into consideration these evidences in order to implement the design of interventions aimed at promoting physical activity of elderly people.